2007
DOI: 10.1016/j.cpr.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A review of successful aging models: Proposing proactive coping as an important additional strategy

Abstract: Successful aging is an important concept, and one that has been the subject of much research. During the last 15 years, the emphasis of this research has shifted from formulating criteria for successful aging to describing the processes involved in successful aging. The main purpose of the present article is to review psychological models of successful aging. The model of Selective Optimization with Compensation (SOC-model) proves to be one of the leading models in this field. Although evidence about its value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
150
3
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(176 citation statements)
references
References 58 publications
12
150
3
8
Order By: Relevance
“…A criticism of the theory is that it is a bit reactive rather than proactive. Ouwehand et al [48] argue that theories or models that focus on proactive coping may lead to greater understanding of successful aging.…”
Section: Psychosocial Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…A criticism of the theory is that it is a bit reactive rather than proactive. Ouwehand et al [48] argue that theories or models that focus on proactive coping may lead to greater understanding of successful aging.…”
Section: Psychosocial Theoriesmentioning
confidence: 99%
“…Paring down the social network to reflect social priorities, focusing on more emotionally riveting content due to the perception of limited time left [48,49].…”
Section: Socioemotional Selectivity Theory (Sst)mentioning
confidence: 99%
“…The studies we have identified on the Spanish adaptation have exclusively tested the psychometric properties and the factorial structure with adults that have not reached old age. It is important to validate instruments in samples of older adults and especially inventories that measure coping strategies because the elderly have to deal with stressful events and life circumstances that are substantially different from those that younger adults have to cope with (Krzemien et al, 2004;Martin et al, 2008;Menninger, 1999;Ouwehand et al, 2007;Urquijo et al, 2008;Villar, 1997). Thus the present study is the first one in verifying the validity and the reliability of the CSI in an elderly sample.…”
Section: Discussionmentioning
confidence: 99%
“…The study of stressful events and how the elderly cope with them represent an important subject in the gerontological research (Villar, 1997). Aging is not a homogenous process (Ouwehand, De Ridder, & Bensing, 2007) and it can vary depending on the individual's particular circumstances. Elderly people must cope with many age-specific stressful situations such as the loss of economic status due to retiring, increasing number of health problems or the loss of social network and widowhood (Krzemien, Urquijo, & Monchietti, 2004;Martin, Kliegel, Rott, Poon, & Johnson, 2008;Menninger, 1999;Urquijo, Monchietti, & Krzemien, 2008).…”
Section: * Introductionmentioning
confidence: 99%
“…It is acknowledged that preventative activities for successful ageing, in addition to reacting effectively to stressful changes, are important. Ouwehand et al (2007) emphasises that successful ageing must be prepared for long in advance; a happy old age is the criterion and reward of a well-conducted life. At an individual level, the RNID should ensure that each person has a tailored health plan, describing their health status and their particular risks, with a health action plan based on their individual needs, which should be updated at regular intervals or transition points in their lives (DoH, 2001).…”
Section: )mentioning
confidence: 99%